Corrigendum. Issue 5 (September 2018) - Unknown
Keuthen, N.J., Tung, E.S., Woods, D.W., Franklin, M.E., Altenburger, E.M., Pauls, D.L., & Flessner, C.A. (2015). Replication study of the Milwaukee inventory for subtypes of trichotillomania-adult version in a clinically-characterized sample. Behavior Modification . 39(4):580-599. DOI: 10.1177/0145445515580533 The authors regret that there is an error in the first paragraph of page 595. It should read as follows and the changes are shown in bold. "Thus, strategies likely to enhance awareness (e.g., stimulus control and habit reversal) would now be primarily appropriate for those withlow scores on the Intention scale. In summary, pullers with high scores on the Emotion scale andhigh scores on the Intention scale would likely benefit most with ACT or DBT. Pullers withlow scores on the Intention scale and low scores on the Emotion scale would likely profit most from treatment beginning with stimulus control and habit reversal."